Voices at the Margins: Accessing Justice as Women with Disabilities in Nepal (Sambahak: Human Rights Journal, 2025)
Women with disabilities in Nepal face multiple layers of marginalization due to their intersecting identities, particularly gender, caste, geographical location and type of disability. This compounded marginalization not only increases their vulnerability to violence and abuse but also significantly restricts their access to justice. Despite the critical importance of this issue, research on women with disabilities' access to justice remains limited. Existing studies tend to focus separately on disability rights or gender justice rather than examining their intersection. This paper draws on the study conducted in 2025 collaboration with leading organization on disability rights: Access Planet Organization. The study adopted a mixed method approach of survey, case study and key informant interviews focusing on four provinces in Nepal: Gandaki, Koshi, Madhesh, and Karnali.  Findings reveal that Nepal’s justice system is designed from an ableist perspective, assuming that justice seekers are fully physically and emotionally “capable” individuals who can navigate legal mechanisms independently or with family support.